2020
DOI: 10.1016/j.semarthrit.2020.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Is there a bidirectional association between rheumatoid arthritis and periodontitis? A systematic review and meta-analysis

Abstract: Background: Several lines of evidence suggest a bi-directional association between Rheumatoid Arthritis (RA) and Periodontitis (PD). Our aim was to systematically appraise the evidence on the association between RA and PD in terms of clinical and laboratory outcomes. Methods: An electronic search of several databases (PubMed, EMBASE, MEDLINE, LILACS, CINHL, Scopus, Web of Science, The Cochrane Library, OpenGrey and Google Scholar) was conducted up to March 2019 (PROSPERO CRD42018107817) by two independent revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 71 publications
1
44
0
Order By: Relevance
“…The oral sequelae of the disease, that if untreated ultimately leads to tooth loss, increases morbidity, reduces quality of life and work productivity [13]. Current evidence suggests periodontitis as a risk factor for CVDs, metabolic conditions, chronic respiratory and neurological disorders, rheumatoid arthritis, immunity conditions, stress or cancer [14][15][16][17][18][19][20][21]. Similarly, epidemiological and limited interventional studies worldwide have observed an association between periodontitis and hypertension [18,22].…”
Section: Introductionmentioning
confidence: 99%
“…The oral sequelae of the disease, that if untreated ultimately leads to tooth loss, increases morbidity, reduces quality of life and work productivity [13]. Current evidence suggests periodontitis as a risk factor for CVDs, metabolic conditions, chronic respiratory and neurological disorders, rheumatoid arthritis, immunity conditions, stress or cancer [14][15][16][17][18][19][20][21]. Similarly, epidemiological and limited interventional studies worldwide have observed an association between periodontitis and hypertension [18,22].…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis (PD) is a chronic periodontal disease characterized by inflamed gums and bone destruction surrounding the teeth due to a dysbiotic microflora that induces the upregulation of inflammatory mediators [ 5 , 6 ]. The systemic repercussions caused by PD are well established [ 7 , 8 , 9 , 10 , 11 ], and PD has been consistently associated with several chronic diseases [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Furthermore, PD negatively impacts a patient’s oral health-related quality of life (OHRQoL) [ 20 ], though it can be restored after periodontal therapy [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since periodontitis is a chronic inflammatory disease associated with microbial dysbiosis and host-driven tissue destruction (Atieh et al, 2014;Artese et al, 2015;Garde et al, 2019;Baeza et al, 2020) (Darre et al, 2008Engebretson and Kocher, 2013;Faggion Jr. et al, 2016;Ziukaite et al, 2018;Jain et al, 2019) Cardiovascular disease (Mustapha et al, 2007;Paraskevas et al, 2008;Freitas et al, 2012;Teeuw et al, 2014;Munz et al, 2018;Roca-Millan et al, 2018;Joshi et al, 2019;Munoz Aguilera et al, 2020) ( Bahekar et al, 2007;Blaizot et al, 2009;Almeida et al, 2018) Rheumatoid arthritis (Han and Reynolds, 2012;Kaur et al, 2014;Bender et al, 2017;Calderaro et al, 2017;Eskandari-Nasab et al, 2017;Hussain et al, 2020) ( Tang et al, 2017;Qiao et al, 2020) Obesity (Akram et al, 2016) (Papageorgiou et al, 2015) Irritable bowel disease * (Eskandari-Nasab et al, 2017;Papageorgiou et al, 2017;Lauritano et al, 2019;She et al, 2020) Osteoporosis (Kornman, 2008;Darveau, 2010), it is recognized that a single oral pathogen would not be sufficient to induce the most common forms of periodontitis. However, historically there were several studies focused on small subgroups of patients with rapidly progressing bone destruction occurring around certain teeth (molars and incisors), called localized aggressive periodontitis, whi...…”
Section: Microbiological Markersmentioning
confidence: 99%